Handbook of Open Source Tools - Koranne, Sandeep; SpringerLink (Online service) (Boston, MA : Springer US, 2011)
Handbook of Open Source Tools introduces a comprehensive collection of advanced open source tools useful in developing software applications. The book contains information on more than 200 open-source tools which include software construction utilities for compilers, virtual-machines, database, graphics, high-performance computing, OpenGL, geometry, algebra, graph theory , GUIs and more. Special highlights for software construction utilities and application libraries are included. Each tool is covered in the context of a real like application development setting. This unique handbook presents a comprehensive discussion of advanced tools, a valuable asset used by most application developers and programmers; includes a special focus on Mathematical Open Source Software not available in most Open Source Software books, and introduces several tools (eg ACL2, CLIPS, CUDA, and COIN) which are not known outside of select groups, but are very powerful. Handbook of Open Source Tools is designed for application developers and programmers working with Open Source Tools. Advanced-level students concentrating on Engineering, Mathematics and Computer Science will find this reference a valuable asset as well.
Part I Fundamentals -- GNU/Linux Operating System -- Text processing -- Part II Software Engineering and Libraries -- Software Engineering -- Standard Libraries -- Apache Portable Runtime -- Boost C++ Libraries -- Performance Libraries -- Compression Engines -- Application Development Libraries -- Hierarchical Data Format 5 : HDF5 -- Graphics and Image Processing Libraries -- Part III Parallel and System Programming -- Parallel Programming -- Part IV Engineering and Mathematical Software -- Scientific Software -- VLSI CAD Tools -- Math libraries -- Mathematics Software -- Artificial Intelligence and Optimization -- Part V Scientific Visualization -- Information Visualization -- Web and Database Systems -- Conclusion -- Index.
Keywords: Computer science; Software engineering; Information systems; Engineering mathematics; Computer Science; Software Engineering/Programming and Operating Systems; Appl.Mathematics/Computational Methods of Engineering; Programming Techniques; Information Systems Applications (incl.Internet).; Programming Languages, Compilers, Interpreters